2011
DOI: 10.1254/jphs.11039sc
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of Morphine Analgesia by Adjuvant Activation of 5-HT7 Receptors

Abstract: Abstract. Spinal blockade of 5-HT 7 receptors has been reported to inhibit the antinociceptive effect of opioids. In this study, we found that subcutaneous administration of the selective 5-HT 7 receptor agonist E-55888 (10 mg/kg) or the antagonist SB-258719 (5 mg/kg) exerted no effect on the tail-flick test in mice. However, E-55888, but not SB-258719, increased (2.6-fold) the analgesic potency of oral morphine. The potentiating effect exerted by E-55888 was prevented by SB-258719. A pharmacokinetic interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 10 publications
1
23
0
Order By: Relevance
“…In this study, subcutaneous administration of 5-HT 7 receptor agonists was devoid of activity in acute nociceptive tests (i.e., thermal- and formalin-induced phase I nociception), but exerted clear-cut antinociceptive effects in phase II of the formalin test in wild-type mice. These results are in line with previous studies showing that 5-HT 7 receptor agonists and antagonists were ineffective in acute thermal nociceptive pain [4447]. The lack of antinociceptive effects in thermal and phase I formalin-induced nociception, observed when 5-HT 7 receptor agonists were administered, suggests no direct modulation by the 5-HT 7 receptor subtype of acute nociceptive signals coming from small caliber unmyelinated nociceptive afferents.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, subcutaneous administration of 5-HT 7 receptor agonists was devoid of activity in acute nociceptive tests (i.e., thermal- and formalin-induced phase I nociception), but exerted clear-cut antinociceptive effects in phase II of the formalin test in wild-type mice. These results are in line with previous studies showing that 5-HT 7 receptor agonists and antagonists were ineffective in acute thermal nociceptive pain [4447]. The lack of antinociceptive effects in thermal and phase I formalin-induced nociception, observed when 5-HT 7 receptor agonists were administered, suggests no direct modulation by the 5-HT 7 receptor subtype of acute nociceptive signals coming from small caliber unmyelinated nociceptive afferents.…”
Section: Discussionsupporting
confidence: 91%
“…The lack of antinociceptive effects in thermal and phase I formalin-induced nociception, observed when 5-HT 7 receptor agonists were administered, suggests no direct modulation by the 5-HT 7 receptor subtype of acute nociceptive signals coming from small caliber unmyelinated nociceptive afferents. However, activation of spinal 5-HT 7 receptors has been shown to play a role in the antinociceptive effects of opioids [4447]. …”
Section: Discussionmentioning
confidence: 99%
“…30 It should also be mentioned here that adjuvant activation of 5-HT7 receptors potentiated morphine analgesia in an acute thermal nociceptive pain condition. 3 The 5-HT7 receptor agonist per se did not exert a significant antinociceptive effect, and a pharmacodynamic interaction was indicated to be responsible for this potentiation of morphine action. Our suggestion extends these results to include the potential use of 5-HT7 agonists not only for pain alleviation as adjuvants with opioids but also for the treatment of opioid-induced hyperalgesia.…”
Section: -Ht7 Receptors In Nociceptionmentioning
confidence: 95%
“…112 It has been reported that blockade of 5-HT 7 receptors inhibit the opioid analgesia. 113 In addition, evidences indicate that the activation 5-HT 7 receptors decrease morphine withdrawal. 114 Further, coadministration of maprotiline (5-HT re-uptake inhibitor) increases the morphine analgesia by 4-fold in rats.…”
Section: Serotonin Receptors and Opioid Antinociceptive Tolerancementioning
confidence: 99%